A conjecture on the derivative bounds of rational Bézier curves. (2nd January 2016) - Zhang, Ren-Jiang; Jiang, Lei
Abstract : By using a new method and employing some existing identities and elementary inequalities, we prove a conjecture on the derivative bounds of rational Bézier curves in the case of degree .